Pre and post Covid preferences for working from home - Caulfield, Brian; O'Mahony, Margaret (My University, 2024)
Working from home (WFH) is being seen as a potential solution to many contemporary problems from congestion to global warming and work-life balance. Since the 1970 s, it was assumed that when information technology had developed enough to enable meaningful real-time communication between an employee in their home and a central workplace, there would be a mass uptake of WFH. However, this promise remained largely unfulfilled until the COVID-19 pandemic, where WFH was mandated for workers for whom it was possible. In this research, the results of two surveys conducted in Ireland in June 2019 and July 2020 examining WFH are analysed using cluster analysis and multinomial logistic regression. The paper investigates the factors that impact the desire to WFH more, and how this has changed from 2019 to 2020. In doing this, the impact of the COVID-19 pandemic and the associated normalisation of WFH are assessed. Key variables included in cluster analysis were identified as the participant’s age and the time taken to complete their daily commute, with younger people and those with longer commutes included in the cluster with those who would like to work from home more. The composition of the clusters remained roughly the same between the 2019 and 2020 surveys. These factors were also included in the multinomial logistic analysis where it was shown that attitudes changed between the two samples, and in 2020 females, those in the older age categories and public transport users had a greater desire to WFH.
PUBLISHED
Keywords: Working from home; Travel demand management; Transport policy; Smart & Sustainable Planet; BEHAVIOR; Environmental Impacts of Transport; Environmental aspects of transportation; Transport; Transport